Geographical distribution of dental caries in children in the southern region of Brazil - Paula Rosalen; Andressa Bulegon; Mayara Trapp Vogel; Lilian Rigo (Universidade Estadual de Maringá, 2023)
The objective was to investigate the experience and severity of dental caries, from the medical records of children who visited the Children's Dental Clinic of a Faculty of southern Brazil, for four years. A cross-sectional study was carried out by analyzing 262 medical records containing information sociodemographic, as well as clinical oral data, to investigate dental caries. Amongst all children included in study, 226 (86.3%) had some teeth with experience of dental caries and 161 (61.5%) had three or more dental caries. The mean dental caries in children aged between 6-8 years was 5.3 ± 3.1, and the average in children aged between 9-12 years was 2.0 ± 1.9. There was association between the severity of dental caries (more than three teeth) and not using dental floss, as well as with the geographical location of residence. Older children were considered to be protected from dental caries. In this study, the experience of dental caries was high, especially in primary teeth, and variables such as the geographical location of residence, absence of flossing were related to the greater severity of dental caries.